A randomized phase II study of full dose gemcitabine versus reduced dose gemcitabine and nab-paclitaxel in vulnerable patients with non-resectable pancreatic cancer (DPCG-01) - Louise Skau Rasmussen; Stine B. Winther; Inna M. Chen; Britta Weber; Lise Ventzel; Gabor Liposits; Julia Sidenius Johansen; Sönke Detlefsen; Ida Egendal; Susy Shim; Signe Christensen; Per Pfeiffer; et al. (BMC Cancer, 2023)
Abstract Background According to current evidence, the best treatment for fit patients with non-resectable pancreatic cancer (PC) is combination chemotherapy, whereas frail patients are recommended gemcitabine (Gem) monotherapy. Randomized controlled trials in colorectal cancer and a post-hoc analysis of gemcitabine and nab-paclitaxel (GemNab) in PC suggest, however, that reduced dose of combination chemotherapy may be feasible and more efficient compared to monotherapy in frail patients. The aim of this study is to investigate whether reduced dose GemNab is superior to full dose Gem in patients with resectable PC, who are not candidates for full dose combination chemotherapy in first line. Methods The Danish Pancreas Cancer Group (DPCG)-01 trial is a national multicenter prospective randomized phase II trial. A total of 100 patients in ECOG performance status 0–2 with non-resectable PC, not candidate for full dose combination chemotherapy in first line, but eligible for full dose Gem, will be included. Patients are randomized 1:1 to either full dose Gem or GemNab in 80% of recommended dose. The primary endpoint is progression-free survival. Secondary endpoints are overall survival, overall response rate, quality of life, toxicity and rate of hospitalizations during treatment. The correlation between blood inflammatory markers, including YKL-40 and IL-6, circulating tumor DNA, and tissue biomarkers of resistance to chemotherapy and outcome will be explored. Finally, the study will include measures of frailty (G8, modified G8, and chair-stand-test) to assess whether scoring would enable a personalized allocation to different treatments or indicates a possibility for interventions. Discussion Single-drug treatment with Gem has for frail patients with non-resectable PC been the main treatment option for more than thirty years, but the impact on outcome is modest. If improved results and sustained tolerability with reduced dose combination chemotherapy can be shown, this could change the future practice for this increasing group of patients. Trial registration ClinicalTrials.gov Identifier: NCT05841420. Secondary Identifying No: N-20210068. EudraCT No: 2021–005067-52. Protocol version: 1.5, 16-MAY-2023.